Ageing bone fractures: the case of a ductile to brittle transition that shifts with age - Zioupos, Peter; Kirchner, Helmut O. K.; Peterlik, Herwig (Elsevier, 2019)
Human bone becomes increasingly brittle with ageing. Bones also fracture differently under slow and fast loadings, being ductile and brittle, respectively. The effects of a combination of these two factors have never been examined before. Here we show that cortical bone is most fracture-resistant at the physiologically prevalent intermediate strain rates of 10−3 s−1 to 10−2 s−1 such as they occur in walking or running, slightly weaker at slower quasistatic and much weaker at fast impact loading rates. In young cortical bone (15 years of age) the ductile-to-brittle transition (DBT) occurs at strain rates of 10−2 s−1, in old cortical bone (85 yrs) at speeds lower by a factor of 10 to 40. Other research has shown that the energy required to break bone (per unit of fracture surface) drops as much as 60% between these two ages. Therefore, DBT seems to compound the well-known phenomenon of ‘brittle old bones’. Old bones can only cope with slow movement, young ones with both slow and fast movement. These observed material characteristics of (i) a shift of the DBT and (ii) a reduced energy absorption capacity appear to contribute at least as much to the loss of bone quality as the various quantity based (lowered bone density and mineral content) explanations of the past. They also provide a new powerful paradigm, which allows us to demonstrate mechanically, and uniquely, how human bone becomes increasingly brittle with age.
Keywords: Bone; Ageing; Toughness; Strain rate; Fractures; Biomechanics; Evolution